Posture During Piano Performance: Variability and Postural Changes Following Training in the Alexander Technique - Wong, Grace K. (Université d'Ottawa / University of Ottawa, 2022)
Musicians can develop and suffer from playing-related musculoskeletal disorders (PRMDs) with pianists being a group of instrumentalists that experience a higher occurrence of PRMDs in comparison with other musicians. One cause of PRMDs is posture. The Alexander Technique (AT) is a popular somatic method among musicians that purports to alter its students’ postural and movement behaviour. Such changes may be beneficial in improving music performance. However, there is a lack of quantitative research to offer support for the effectiveness of the AT in altering posture in musicians, especially in pianists. To address this issue, four studies were conducted. The first study addressed the AT alone to determine what postural changes could be expected following lessons in the AT. Findings of this study showed that changes include a larger craniovertebral angle, head tilt, and head-neck-trunk angle as well as smaller trunk, thoracic, and thoracolumbar angles. The second study addressed variability in individual pianists’ postures and its implications for intervention studies. The results of this study demonstrated that within-person variability is present in posture between performances but does not vary widely enough to exhibit inconsistent posture across measurements. The third study examined the effects of 10 AT lessons on pianists’ postures. Findings showed that, in comparison with their pre-lesson measurements, pianists demonstrate a postural pattern of larger craniovertebral and head-neck-trunk angles as well as smaller trunk, thoracic, and thoracolumbar angles in both the post-test and follow-up tests. The fourth study explored the relationship between pianists’ perceptions of their posture and their application of the AT with quantitatively measured changes in their posture. The results of this study showed that participant perception and reported application of the AT does not necessarily always reflect the postural changes that have occurred.
Keywords: posture; pianists; Alexander Technique; spinal angles; variability; intraindividual variability; perception